PENTINGNYA PENGAWASAN, KETAATAN PERATURAN, KEJELASAN SASARAN ANGGARAN, DAN PEMANFAATAN TEKNOLOGI INFORMASI PADA AKUNTABILITAS KINERJA INSTANSI PEMERINTAH : THE IMPORTANCE OF SUPERVISION, REGULATION COMPLIANCE, CLARITY OF BUDGET TARGETS, AND UTILIZATION OF INFORMATION TECHNOLOGY IN GOVERNMENT AGENCY PERFORMANCE ACCOUNTABILITY - Khairani, Annisa; Wancik, Zulkifli; Oktarida, Anggeraini (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
This research aims to determine the impact of the Role of Government Internal Supervisory Apparatus, Compliance with Regulations, Clarity of Budget Targets, and Utilization of Information Technology on the Performance Accountability of Government Agencies within the Regional Apparatus Organization of Palembang City. The methodology used is a quantitative approach, collecting data primarily from Regional Apparatus Organization in Palembang City. A total of 124 responses were gathered from 26 selected samples out of distributed questionnaires. The research employs multiple linear regression analysis with IBM SPSS version 27 to conduct hypothesis testing. The analysis show that the variables—Role of Government Internal Supervisory Apparatus, Compliance with Regulations, Clarity of Budget Targets, and Utilization of Information Technology—have a significant influence on the Performance Accountability of Government Agencies in Palembang City.